2001
DOI: 10.1515/cclm.2001.068
|View full text |Cite
|
Sign up to set email alerts
|

The Friedewald Formula Underestimates LDL Cholesterol at low Concentrations

Abstract: Due to recent advances in the treatment of hypercholesterolemia, low density lipoprotein (LDL) cholesterol concentrations below 2.6 mmol/l have become attainable. In general, LDL cholesterol is determined indirectly according to Friedewald. We examined the performance of the Friedewald formula at low concentrations of LDL cholesterol in comparison with a beta-quantification method. We analyzed 176 samples from individuals treated by LDL apheresis with a mean LDL cholesterol concentration of 3.07 mmol/l and fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
1
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(75 citation statements)
references
References 34 publications
2
69
1
3
Order By: Relevance
“…The Friedewald formula was previously shown to incorrectly estimate LDL-C at the lowest TG levels [8,10] de Cordova (Wako) [33].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Friedewald formula was previously shown to incorrectly estimate LDL-C at the lowest TG levels [8,10] de Cordova (Wako) [33].…”
Section: Resultsmentioning
confidence: 99%
“…The formula requires fasting plasma high density lipoproteincholesterol (HDL-C), total cholesterol (TC), and TG, and is calculated as LDL-C = TC -HDL -(TG/5) for mg/dl (2.2 in mmol/l). This formula is less accurate in extremes of TG or TC values [7][8][9][10] or in patients with co-morbidities (eg. renal failure or diabetes) [2,11], but is widely used.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that calculated LDL-C by Friedewald significantly underestimates LDL-C compared with the ultracentrifugation method in patients with very low LDL-C, 25,26 resulting in an overestimation of reduction when LDL-C falls below 1.8 mmol/L (70 mg/dL). In this study, reductions at 2 weeks using calculated LDL-C were in excess of 60% for both doses of AMG 145, and the reduction in the primary end point, LDL-C measured by ultracentrifugation, achieved with Q4W dosing of 420 mg AMG 145 was at least comparable with that achieved with Q2W dosing and better than that achieved with Q4W dosing of REGN727 in similarly statin-treated FH patients.…”
Section: Discussionmentioning
confidence: 99%
“…It should not be used if patients are nonfasting, if triglycerides are Ͼ400 mg/dL (4.52 mmol/L), or if the patient has type III hyperlipoproteinemia. The equation is increasingly inaccurate with triglycerides Ͼ200 mg/dL (2.26 mmol/L) (81,82 ) and at relatively low LDL-C concentrations (83 ). The Friedewald formula is based on the measurement of total cholesterol, triglycerides, and HDL-C.…”
Section: Measurement Issuesmentioning
confidence: 99%